PENGGUNAAN SARANA MEDIA ELEKTRONIK MERDEKA BELAJAR DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN ISLAM DI SMP NEGERI 22 PALEMBANG - Ahmad Zainuri (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
The Covid-19 pandemic has changed many aspects of human life, one of which is education. The Ministry of Education and Culture, is in a position to decide on distance learning which is a type of asynchronous learning as the most appropriate option during the COVID-19 pandemic. With various considerations, in the end, the concept of Merdeka Belajar found a massive acceleration movement in the midst of its emergence as a government regulation that was just rolled out last December 2019. The concept of Merdeka Belajar is also applied to Islamic education learning. This research includes research using descriptive qualitative methods with the aim of analyzing the use of Merdeka Belajar electronic media facilities used in Islamic religious learning.The results showed that from the teacher's side, the application of free electronic media to learn in learning activities has advantages where teachers become more creative and innovative thinking than before because independent learning makes teachers think freely or independently in how teachers make learning goals achievable by all students without exception. However, there are obstacles such as Islamic religious education teachers who have been teaching for a long time, there are difficulties in adapting to free electronic media for learning. The teachers who experience this are on average Islamic religious education teachers who are seniors in school and not all students have gadgets that meet the required capacity. So there is still a need for solutions in dealing with existing obstacles